A solution to the Lifely Disobedience and its Effect to Stop Divorce (Journal of the College of Education for Women, 2019)
Allah legislated marriage and made it dwelling, fellowship and mercy betweenthe two couples, Prophet Moh'd (peace of Allah and blessing be upon him) ordered ahusband to look after his wife, treat her with full charity and make love with hereevery kindly. On the other hand, he ordered a wife to obey her husband and respecthim deeply, nevertheless, some obstacles may sometimes be appeared within the lifeof their marriage, this may be caused by either a husband or a wife. This problem iscalled lifely disobedience (AL-Noshooz).In the other words, this means that a wife begins to hate her husband, refuse his ordersand not obey him.In brief, they hate each other which leads to some marks appear in theirmanners and bahaviours, for example, a wife refuses her husband's requests, ordersand commands and so does the husband, he begins to leave her in bed and ignore herin treatment. The researcher explained a solution to the problem of disobedience afterhe had mentioned the types of it that might be appeared in the manners or behavioursof both a wife or a husband. This clear solution comes from the holy Quran, Prophet'stradition (Hadith) and Muslim Scientists, points of view, the researcher alsomentioned how a husband may do towards manipulating this problem according to theinstructions of Holly Quran and the Islam teaching first, a husband is ordered toadvise his wife about the dangers of divorce and reminds her about Allah'spunishment in the day of judgment. Then the researcher mentioned the second stepwhich a husband may follow to avoid divorcing as ignoring her in bed.This step seems to be more serious than the previous one. After the researcherhad explained everything about how to solve this problem in these previous stepsaccording to the Holy Quran, Prophets Traditions and Muslim Scientists gradually, Hementioned the third step which is hitting the husband should avoid hitting hisdisobedient wife on her face, sensitive areas and infront of people, hitting wivesshouldn't be more than ten flippings or whipping. The fourth step of solving theproblem of disobedience is judging. Two persons judged between the two couplesafter hearing their complaints and the reason of this problem. One person belongs to ahusband's family and the other belongs to a wif's family or relatives.Finally, the researcher mentioned the husband's lifely disobedience, it'slimitations, treatment, conclusion, and the most important results